Integrated framework for rapid climate stress testing on a monthly timestep. (April 2022) - Fowler, Keirnan; Ballis, Natasha; Horne, Avril; John, Andrew; Nathan, Rory; Peel, Murray
Abstract: "Bottom-up" methods are increasingly used to assess the vulnerability of water systems to climate change. Central to these methods is the climate "stress test", where the system is subjected to various climatic changes to test for unacceptable outcomes. We present a framework for climate stress testing on a monthly timestep, suitable for systems whose dominant dynamic is seasonal or longer (eg. water resource systems with carry-over storage). The framework integrates multi-site stochastic climate generation with perturbation methods and in-built rainfall runoff modelling. The stochastic generation includes a low frequency component suitable for representing multi-annual fluctuations. Multiple perturbation options are provided, ranging from simple delta change through to altered seasonality and low frequency dynamics. The framework runs rapidly, supporting comprehensive multi-dimensional stress testing without recourse to supercomputing facilities. We demonstrate the framework on a large water resource system in southern Australia. The Matlab/Octave framework is freely available for download from https://doi.org/10.5281/zenodo.5617008 . Highlights: We present a freely available framework for climate stress testing of water systems. The framework includes stochastic climate generation, rainfall-runoff modelling, and perturbation for five stressors. The monthly timestep allows rapid run-times, providing greater possibilities for a given computational budget.